Studi Perbandingan Sistem Peradilan Indonesia Dan Malaysia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research is a comparative study of two laws in the world, namely Indonesian law and Malaysian law. The two studies were carried out in comparing the definitions, characteristics, objectives and legal systems of judicial structures. This research aims to compare the two to find possible advantages and disadvantages, especially regarding the criminal justice system as well. By comparing the Malaysian legal system, Indonesia is no worse than Malaysia. In this research it turns out that Indonesia has many advantages, namely people who work and work in the legal field, and therefore it is possible that the rule of law in Indonesia is still better because there are many people who law-abiding. The Indonesian state must create a good legal system, the court structure must take into account the culture of a society like Malaysia, because law enforcement will be more effective if it is in accordance with the values ​​or customs that have been formed in the society itself.